Job satisfaction among Ethiopian nurses: a systematic review - Habtamu Abera Areri; Animut Alebel; Luel Deribe (Sciendo, 2021)
Job satisfaction is a positive emotional feeling in the working environment, and it is an essential tool with which to improve patient safety, nurses' efficiency and performance, quality of care, retention and turnover of nurses, and commitment to the organization and the profession. There are few studies on job satisfaction of nurses in the country. Therefore, this review aims to estimate the pooled prevalence of job satisfaction among Ethiopian nurses using the available studies.